Synthesis and characterization of six-membered pincer nickelacycles and application in alkylation of benzothiazole - Pandiri, H.; Sharma, D.M.; Gonnade, R.G.; Punji, B. (Journal of Chemical Sciences, 2017)
Six-membered pincer nickelacycle complexes have been synthesized and employed for the catalytic C–H bond alkylation of benzothiazole. The pincer nickelacycle, {κP, κC, κP- (2 - iPr 2POCH 2-C 6H 3- 6 -CH 2OP iPr 2)} NiBr , [(iPr4-POCCCOP)NiBr(2)] was synthesized by the reaction of 1,3 - iPr 2POCH 2-C 6H 4-CH 2OP iPr 2[(iPr4-POCCCOP)-H(1)] with (CH3CN)2NiBr2 in the presence of Et 3N via the C(2)–H activation on ligand 1. Treatment of [(iPr4-POCCCOP)NiBr](2) with AgOAc afforded the complex [(iPr 4-POCCCOP) Ni (OAc)] (3) in good yield. Both the complexes 2 and 3 were characterized by 1H , 13C and 31P -NMR spectral analysis. Further, the molecular structures of complexes 2 and 3 were established by X-ray crystallography. The complex 2 was found to be an active catalyst for the C–H bond alkylation of benzothiazole with alkyl halides containing β–hydrogen atoms. Graphical abstract: Synopsis. Six-membered pincer nickelacycles have been synthesized and structurally characterized, which show catalytic activity for the C–H bond alkylation of benzothiazole with alkyl halides containing β–hydrogen atoms.[Figure not available: see fulltext.].
Keywords: Active catalyst; Alkyl halides; Alkylation; Atoms; Benzothiazole; Benzothiazoles; Catalyst activity; Chemical activation; Crystallography; C–H activation; Hydrogen atoms; Nickelacycles; Pincer complex; Pincer complexessix-membered nickelacycle; six-membered nickelacycle; Spectrum analysis; Synthesis (chemical); Synthesis and characterizations; X ray crystallography

Potassium phosphate catalyzed highly efficient synthesis of structurally diverse thioethers at ambient temperature - Mitragotri, Satish D.; Kulkarni, Makarand A.; Desai, V. Uday; Wadagaonkar, Prakash P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2022)
Commercially available potassium phosphate has been demonstrated to be a highly efficient catalyst for the synthesis of thioethers employing two different routes viz. alkylation of thiols with alkyl/aralkyl halides and by Michael addition of thiols to conjugated alkenes.
Keywords: Alkyl halides; Potassium phosphate; thia-Michael reaction; thioethers; thiols

Rongalite as a sulfone source: sulfonylation of para-quinone methides and alkyl/allyl halides - Kale, Someshwar B.; Jori, Popat K.; Das, Utpal (Chemistry-an Asian Journal, 2022)
A one-pot three-component reaction using p-quinone methides, rongalite and alkyl/allyl halides has been described. The corresponding unsymmetrical sulfones were obtained in good yields under mild reaction conditions in the absence of any metal, base or any other additive.
Keywords: Alkyl halides; diaryl methine; p-Quinone methide; rongalite; sulfonylation